Why Chinese Consumers Prefer Housing Ownership to Renting Before Marriage: An investigation of Chinese young consumers' rent-versus-buy housing decisions - Du, Mingjie (2010)
This paper aims to investigate the influential factors of Chinese young consumers’ rent-versus-buy housing decisions before marriage, and thus to explain why most Chinese consumers prefer housing ownership to renting or even regard an own-occupied housing as a prerequisite of marriage. The research was based on rich literatures concerning rent-versus-buy housing decisions and consumer decision making theory. A qualitative approach was adopted to conduct the research to gain in-depth insight of consumer behaviour under certain circumstance. 12 interviews were undertaken with the young singles and another 3 were with the parents to further understand the impact of family as a significant reference group. The respondents were mainly selected via personal links and a snowball effect was utilized afterwards. The interview outcome confirms the preference of housing ownership among Chinese young consumers before marriage and demonstrates several possible determinants of its popularity. Culture acts as the most deeply-rooted factor that shapes Chinese consumers’ perception and attitudes toward housing ownership and renting. Other external factors such as socio-economics, public policy and reference group respectively exert influences on the rent-versus-buy housing decisions before marriage to difference extents. With regard to internal influential factors, motivation and attitudes intrinsically affect Chinese consumer decisions to rent or purchase a house. The four external and two internal factors jointly shape Chinese young consumers’ rent-versus-buy housing decisions before marriage. To tackle with the overheating problem in real estate market, government entities should take the responsibility to introduce various policies to foster the development of property rental market and thus adjust the market supply and demand equilibrium.